2020
DOI: 10.21037/atm-19-4763
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto’s thyroiditis might increase polycystic ovary syndrome and associated comorbidities risks in Asia

Abstract: Background: To investigate whether increased the comorbidities such as coronary artery disease (CAD) and risks between Hashimoto's thyroiditis (HT) and polycystic ovary syndrome (PCOS) in Taiwanese women.Methods: Patients newly diagnosed as having HT during 2000-2012 were assigned to the case group.Cases and controls were matched for age and comorbidities at a 1:2 ratio using propensity score matching.Incidence was calculated in the unit of 1000 person-year. Univariate and multivariate Cox proportional haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Its key characteristics are persistent anovulation, hyperandrogenism, and insulin resistance. The main manifestations are menstrual disorders and reproductive dysfunction (2)(3)(4), one of the leading causes of females in anovulatory infertility (5,6). The World Health Organization estimates PCOS has affected over 116 million women worldwide as of 2010 (7).…”
Section: Introductionmentioning
confidence: 99%
“…Its key characteristics are persistent anovulation, hyperandrogenism, and insulin resistance. The main manifestations are menstrual disorders and reproductive dysfunction (2)(3)(4), one of the leading causes of females in anovulatory infertility (5,6). The World Health Organization estimates PCOS has affected over 116 million women worldwide as of 2010 (7).…”
Section: Introductionmentioning
confidence: 99%
“…It can also increase the risk of mood disorders, cardiovascular and cerebrovascular diseases, type 2 diabetes, venous thromboembolism, pregnancy diseases, endometrial cancer, and other diseases (1)(2)(3). The pathogenesis of PCOS has not been fully elucidated, but current studies have shown that HA, inflammation, and oxidative damage jointly play a vicious cycle in the pathophysiology of the disease (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…(PCOS) (3). A potentially helpful alternative for women with PCOS is to remove mature oocytes from small antral follicles early, without hormone stimulation, and then perform in vitro maturation (IVM) of oocytes (4).…”
Section: Introductionmentioning
confidence: 99%